Malathion-induced spermatozoal oxidative damage and alterations in sperm quality of endangered trout Salmo coruhensis - Kocabas, Mehmet; Kutluyer, Filiz; Benzer, Fulya; Erisir, Mine (Springer Heidelberg, 2018)
The use of pesticides has been increased along with increasing the farming activities and has caused environmental impacts deleteriously. In particular, non-target organisms including fish can be affected by toxic effects of pesticides. Therefore, the impacts of malathion (MTN) on oxidative stress and sperm quality were investigated in vitro. The MTN concentrations used on this study were 0 (control), 75, 100, and 125 mu g/L. Lipid peroxidation (MDA), non-enzymatic (GSH), and enzymatic (SOD, GSH-Px, and CAT) activities in spermatozoa were examined for determination of oxidative stress status. Our findings showed that motility rate and period of sperm cells significantly decreased with exposure to MTN. Biochemical assays revealed that CAT activity and levels of MDA, GSH increased in spermatozoa based on concentration while activity of GSH-Px and SOD decreased. Consequently, spermatozoa were highly sensitive to MTN exposure. MTN has disruptive effects on sperm quality and caused to oxidative stress in spermatozoa.
Keywords: Malathion; Endangered trout; Oxidative stress parameters; Salmo coruhensis; Sperm cell